An Anomalous Electron Configuration Among 3d Transition Metal Atoms. Issue 7 (12th January 2023) - Tang, Zhexin; Shang, Tongtong; Xu, Han; Lin, Ting; Gao, Ang; Lin, Weiguang; Li, Xinyan; Wang, Shiyu; Yu, Botao; Meng, Fanqi; Zhang, Qinghua; Wang, Xuefeng; et al.
Abstract: Physical properties of materials are mainly determined by valence electron configurations, where different valence shells would induce divergent phenomena. In compounds containing Sc 2+, 3 d electron occupancy is expected, the same as other transition metal atoms like Ti 3+ . But this situation still awaits experimental verification in inorganic materials. Here, we selected ScS to measure the valence electron density and orbital population of Sc 2+ through delicate quantitative convergent‐beam electron diffraction. With the absence of 3 d orbital features around Sc‐atom sites and the nearly bare population of t2g orbital, the unintuitive occupation of 4 s orbital in Sc 2+ is concluded. It should be the first time to report such a special electron configuration in a transition metal compound, in which 4 s rather than 3 d orbital is preferred. Our findings reveal the distinct behavior of Sc and probable ways to modulate material properties by controlling electron orbitals. Abstract : A special [Ar]4 s 1 electron configuration was revealed for Sc 2+ in ScS, with no typical 3 d orbital features and a bare population of t2g orbital from electron density reconstruction and orbital population analysis. Our work should be the first to report such anomalous electron structure with preferred 4 s over 3 d orbital for 3 d transition metal atoms and may provide a new method to modulate material properties via artificial orbital adjustment.